Familial Interstitial 6q23.2 Deletion Including Eya4 Associated With Otofaciocervical Syndrome - Gana, Simone; Valetto, Angelo; Toschi, Benedetta; Sardelli, Irene; Cappelli, Susanna; Peroni, Diego; Bertini, Veronica (Frontiers in Genetics, 2019)
We report on a 34-year old woman and her mother who both have clinical features suggestive for otofaciocervical syndrome (OTFCS), a disorder characterized by a combination of facial dysmorphisms , ear abnormalities with hearing loss and shoulder girdle anomalies. OTFCS presents overlapping features with branchiootorenal spectrum disorders , including branchiootorenal syndrome and branchiootic syndrome . These disorders have been described as clinically distinct entities, but molecular studies have shown that all the causative genes belong to Pax-Six-Eya-Dach network (PSEDN). So far, the genetic diagnosis of OTFC has been performed only in very few cases and involves two genes, EYA1 and PAX1, thus it is likely that other genes have still to be identified. In present patient, array CGH analysis showed a 3.7 Mb deletion in 6q23; a smaller 1.9 Mb deletion in the same region was detected in her mother. The minimal overlapping region harbours the EYA4 gene. The cases here described are interesting, since they all showed the typical clinical features of OTFCS, associated to a deletion in 6q23.2. Even if we can not exclude the contribution of other genes to the phenotype, EYA4 is a good candidate for OTFCS according to its pattern of expression, its sequence similarity to EYA1, and its involvement in PSEDN.